Residual effect of raw material of chitosan powder on chemical properties of soil under rice-rice cropping system (Research in Agriculture Livestock and Fisheries, 2020)
The experiment was conducted at the research field of Sher-e-Bangla Agricultural University, Dhaka- 1207, Bangladesh, during 2015-2016, to investigate residual effect of raw material of chitosan (CHT) powder on chemical properties of rice growing soils. The field experiment was done using BRRI dhan29. The experiment was laid out in randomized complete block design (RCBD) with four replications. The first experiment was done using four different doses of the raw material of CHT powder with one control. The treatments were as follows: T1= 0.5 t/ha, T2 = 1.0 t/ha, T3 = 2.0 t/ha, T4 = 4.0 t/ha and T5 = 0 t/ha. The second experiment was conducted in the same plot using the following treatments were T1= Residual effect of the raw material of CHT powder @ 0.5 t/ha (applied in the previous experiment) + 2/3rd of recommended N fertilizer, T2 = Residual effect of the raw material of CHT powder @ 1.0 t/ha (applied in the previous experiment) + 2/3rd of recommended N fertilizer, T3 = Residual effect of the raw material of CHT powder @ 2.0 t/ha (applied in the previous experiment) + 2/3rd of recommended N fertilizer, T4 = Residual effect of the raw material of CHT powder @ 4.0 t/ha (applied in the previous experiment) + 2/3rd of recommended N fertilizer and T5 = Residual effect of the raw material of CHT powder @ 0 t/ha + recommended N (control). The total nitrogen content, soil pH, organic carbon and organic matter status in the post-harvest-soils were increased due to the residual effect of the powder in rice growing soils. The maximum value of the pH (7.01), organic carbon content (0.72%), and organic matter content (1.24%) in the post-harvest soils were found in the treatment T4 and lowest values were observed in the control treatment (T5). From the results it could be concluded that some of the chemical properties of rice growing soils were improved due to the residual effect of the raw material of CHT powder. Residual nitrogen value indicates that the raw material of CHT powder has a slow releasing effect of organic nitrogen supplementation in soil. These results suggest that the residual effect of the raw material of CHT powder could play a significant role to improve the sustainable soil health.Res. Agric., Livest. Fish.7(1): 33-42, April 2020